2019
DOI: 10.1038/s41598-019-56886-x
|View full text |Cite|
|
Sign up to set email alerts
|

Regulatory Role of PlaR (YiaJ) for Plant Utilization in Escherichia coli K-12

Abstract: Outside a warm-blooded animal host, the enterobacterium Escherichia coli K-12 is also able to grow and survive in stressful nature. The major organic substance in nature is plant, but the genetic system of E. coli how to utilize plant-derived materials as nutrients is poorly understood. Here we describe the set of regulatory targets for uncharacterized IclR-family transcription factor YiaJ on the E. coli genome, using gSELEX screening system. Among a total of 18 high-affinity binding targets of YiaJ, the major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…YhjC was renamed as RcdB (regulator B of the csgD promoter) while as to YiaJ, we recently identified its involvement in regulation of plant utilization (utilization of plant nutrients and colonization in plants) by E. coli and therefore renamed it as PlaR (regulator of plant utilization) [28]. The csgD promoter has been recognized as the most complex ‘multi-factor’ promoter in E.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…YhjC was renamed as RcdB (regulator B of the csgD promoter) while as to YiaJ, we recently identified its involvement in regulation of plant utilization (utilization of plant nutrients and colonization in plants) by E. coli and therefore renamed it as PlaR (regulator of plant utilization) [28]. The csgD promoter has been recognized as the most complex ‘multi-factor’ promoter in E.…”
Section: Resultsmentioning
confidence: 99%
“…Recently we found that YiaJ plays a regulatory role in expression of a set of the genes for the utilization of plant-derived materials as nutrients for survival outside host animals, and a group of the genes for colonization within plants under stressful environments in nature, including the formation of biofilm [28]. We then renamed YiaJ to PlaR (regulator of plant utilization).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They find that they can obtain strong evidence for two of these uncharacterized TFs, YiaJ (PlaR) and YhjC (RcdB), regulating the csgD promoter. For RcdB this is the first evidence for any promoter it regulates, while PlaR is a TF that they think from a related study is involved in regulating operons involved in the utilization of plant-derived nutrients, although this still needs further study [8]. The study reminds us that we still have plenty of biology to learn from this model organism, over 20 years after its genome was sequenced.…”
Section: Full-textmentioning
confidence: 93%
“…Table 1). A collection of 500-bp sequences from these targets was analysed using the dminda 2.0 program, which was successfully employed for the identification of the PlaR (regulator of plant utilization)-box sequence [13]. We identified a 17-bp-long sequence ( Fig.…”
Section: Consensus Recognition Sequence Of Pdhrmentioning
confidence: 99%